2020
DOI: 10.21203/rs.3.rs-38372/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Independent and interactive effect of sitting time and physical activity on prevalence of hyperuricemia: the Henan Rural Cohort Study

Abstract: Background. There are few studies on the hyperuricemia (HUA) and moderate to vigorous intensity physical activity (PA) and also hardly regarding sitting time (ST). The purpose of this study was to examine the independent and interactive association of PA and ST with HUA.Methods. A cross-sectional analysis was performed on 38,855 participants (aged 18-79) enrolled from the Henan Rural Cohort Study at baseline (2015 to 2017). PA and ST levels were assessed by using the International Physical Activity Questionnai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…In our study, although less physical activity significantly increased the risk of hyperuricaemia in univariate analysis, the relationship between physical activity and hyperuricaemia was not significant in multivariate analysis after adjustment of the effect of overweight/obesity and hypertension variables. Dong et al, 22 in a study of 38,855 rural China populations, showed that regular physical activity independently reduced serum uric acid levels and the prevalence of hyperuricaemia. However, in the regression analysis performed in the study of Dong et al, 22 adjustment was done for BMI but not for hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, although less physical activity significantly increased the risk of hyperuricaemia in univariate analysis, the relationship between physical activity and hyperuricaemia was not significant in multivariate analysis after adjustment of the effect of overweight/obesity and hypertension variables. Dong et al, 22 in a study of 38,855 rural China populations, showed that regular physical activity independently reduced serum uric acid levels and the prevalence of hyperuricaemia. However, in the regression analysis performed in the study of Dong et al, 22 adjustment was done for BMI but not for hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Dong et al, 22 in a study of 38,855 rural China populations, showed that regular physical activity independently reduced serum uric acid levels and the prevalence of hyperuricaemia. However, in the regression analysis performed in the study of Dong et al, 22 adjustment was done for BMI but not for hypertension. In the study by Qi et al, 10 low physical activity in men was associated with an increased risk of high uric acid levels.…”
Section: Discussionmentioning
confidence: 99%